Structural Reforms in the Eurozone: Timing Matters - David Pothier (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Several leading policymakers - from ECB President Mario Draghi to EC President José Manual Barroso - have pushed Eurozone countries to adopt far-reaching structural reforms in labour and product markets in order to foster growth and employment. While there is a broad consensus that structural reforms enhance countries' growth potential in the long-run, recent research shows that they may have harmful effects in the short-run when not accompanied by substantial monetary stimulus. Consequently, a heated debate has started among economists and policymakers about whether now is the right time for the Eurozone to implement structural reforms. This column offers a brief summary of this debate.
Keywords: 330